Method of singular spectrum analysis with the interval uncertainty for the prediction of agro-climatic conditions - Лєві, Л. І.; Петровський, О. М. (Scientific Progress & Innovations, 2016)
The paper offers a mathematical model for the analysis and prediction of agro-climatic data by singular spectrum analysis (SSA) with the interval uncertainty. The mathematical model is designed to determine the optimal weather conditions at sowing wheat seed which is previously stimulated by electromagnetic field of high frequency. It was shown that pre-sowing seed stimulation leads to an increase of water uptake, nutrients and therefore requires optimum conditions for germination and subsequent plant growth. Mathematical modeling made it possible to predict the required optimum agro-climatic conditions in terms of humidity and soil temperature.